2017
DOI: 10.17240/aibuefd.2017.17.28551-304650
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının Ölçme Ve Değerlendirmeye Yönelik Yeterlik Algılarının İncelenmesi (Kafkas Üniversitesi Örneği)

Abstract: ÖZETBu araştırmanın amacı, Kafkas Üniversitesinde öğrenim gören öğretmen adaylarının ölçme ve değerlendirmeye yönelik yeterlik algılarını ve bu algıların çeşitli değişkenler bakımından farklılık gösterip göstermediğini tespit etmektir. Tarama araştırma modelinde yürütülen çalışmada öğretmen adaylarının ölçme ve değerlendirmeye yönelik yeterlik algılarının belirlenmesinde Nartgün (2008) tarafından geliştirilen, "Ölçme ve Değerlendirme Genel Yeterlik Algısı Ölçeği" kullanılmıştır. Araştırmanın çalışma grubunu 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 2 publications
0
12
0
3
Order By: Relevance
“…In the study "Examination of the Perspectives of Pre-service Teachers on Assessment and Evaluation" conducted by Kubilay and Sabancu (2016), it was determined that pre-service teachers felt themselves "moderately sufficient". In the study "Examination of Efficacy Perceptions of Pre-service Teachers for Assessment and Evaluation (Kafkas University Sample)" by Yaralı (2017), it was concluded that the efficacy perceptions of pre-service teachers for assessment and evaluation were found to be "Sufficient" in the sub-dimension of Basic Concepts, "Moderately Sufficient" in the sub-dimension of Assessment Techniques, and "Moderately Sufficient" in the sub-dimensions of Statistical Analysis and Reporting. Looney et al (2017) argue that more research is needed to shed light on teachers' identities as assessors (i.e., their conceptions, beliefs, experiences, knowledge, skills and feelings) in order to better understand their assessment practice.…”
Section: The Belief Of Self-efficacymentioning
confidence: 99%
“…In the study "Examination of the Perspectives of Pre-service Teachers on Assessment and Evaluation" conducted by Kubilay and Sabancu (2016), it was determined that pre-service teachers felt themselves "moderately sufficient". In the study "Examination of Efficacy Perceptions of Pre-service Teachers for Assessment and Evaluation (Kafkas University Sample)" by Yaralı (2017), it was concluded that the efficacy perceptions of pre-service teachers for assessment and evaluation were found to be "Sufficient" in the sub-dimension of Basic Concepts, "Moderately Sufficient" in the sub-dimension of Assessment Techniques, and "Moderately Sufficient" in the sub-dimensions of Statistical Analysis and Reporting. Looney et al (2017) argue that more research is needed to shed light on teachers' identities as assessors (i.e., their conceptions, beliefs, experiences, knowledge, skills and feelings) in order to better understand their assessment practice.…”
Section: The Belief Of Self-efficacymentioning
confidence: 99%
“…Kız öğrencilerin "temel kavramlar", "ölçme teknikleri" ve "istatistiksel çözümleme ve raporlaştırma" alt boyutlarında yeterlik algıları erkek öğrencilere göre daha yüksektir. Ancak farklı branşlarda yapılan çalışmalarda (Pektaş, 2010;Yaman -Karamustafaoğlu, 2011;Yeşilyurt, 2012;Yaralı, 2017) "cinsiyet" değişkeni ile öğretmen adaylarının genel yeterlik algıları arasında anlamlı düzeyde bir farkın olmadığı sonucuna ulaşılmıştır.…”
Section: Bulgularunclassified
“…Literatürde, öğretmen adaylarının ölçme ve değerlendirme yeterliklerinin incelendiği çalışmalar bulunmaktadır (Özdemir, 2008;Birgin -Gürbüz, 2008;Pektaş, 2010;Yaman -Karamustafaoğlu, 2011;Yeşilyurt, 2012;Şahin -Uysal, 2013;Çalışkan v.dğr., 2013;Yaşar, 2014;Sabancı -Yazıcı, 2017;Demir Atalay, 2017;Yaralı, 2017). Yine Din Kültürü ve Ahlak Bilgisi öğretmenlerinin, ölçme ve değerlendirme alanına yönelik sorunları ve yeterlikleri ile sınırlı sayıda araştırma da yapılmıştır (Güngör, 2001;Rençber, 2010;Çakmak, 2011;Gündoğdu, 2011;Ulu, 2011;Yıldız, 2015 Ölçeği" kullanılmıştır.…”
Section: Introductionunclassified
“…In addition, the gender variable was observed to be another significant variable related to measurement and evaluation competency and which is frequently examined by researchers (Akdağ, 2011;Altun, 2017;Eğri, 2006;Erdoğdu & Kurt, 2012;Günal et. al.2015;Pektaş, 2010;Şimşek, 2018;Yaralı, 2017) In their study, examining the measurement and evaluation competencies of pre-service teachers by various variables, Günal et. al (2015) compared data by gender.…”
Section: Introductionmentioning
confidence: 99%